ANALYSIS OF THE QUESTIONNAIRE FOR ASSESSING THE LEADERSHIP QUALITIES OF STUDENTS - Maslak, Anatoly (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The quality of the questionnaire as a measuring tool largely determines the relevance of the results. The aim of the work is to analyze the quality of the questionnaire as a measuring tool used to evaluate the latent variable "leadership qualities of students". The study was conducted within the framework of the theory of measurement of latent variables, which has important advantages. First of all, the latent variable is determined operationally, through a set of indicators (questionnaire items), the more indicators, the higher the accuracy of the latent variable measurement. The latent variable and indicators are measured on the same interval scale in logits. This allows the use of a wide range of statistical procedures for the analysis of measurement results. The analysis of the following aspects of the quality of the questionnaire as a measuring tool: the presence of extreme indicators in the test, the compatibility of a set of indicators, the compliance of the questionnaire to the level of students on the measured latent variable, the uniformity of the distribution of indicators on the interval scale. The indicators that differentiate students with high and low levels of leadership qualities better than others are highlighted. Recommendations on the adjustment of the questionnaire as a measuring tool for assessing the leadership qualities of students are given.